2010
DOI: 10.1039/b918588g
|View full text |Cite
|
Sign up to set email alerts
|

Practical copper(i)-catalysed amidation of aldehydes

Abstract: The direct synthesis of amides by insertion into the C-H bond of aldehydes is shown to be a practical procedure through application of cheap, readily available catalysts generated in situ from copper(i) halides and pyridine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 38 publications
3
40
0
1
Order By: Relevance
“…A plausible reaction mechanism was proposed as shown in Scheme 1. Similar to previous reports, 5 iron catalysts could decompose PhI=NTs to generate an iron imido/ni-trene intermediate, which may undergo nitrene insertion into the C-H bond of an aldehyde to afford the corresponding amide. Attempts were made to characterize the reaction intermediate by monitoring the reaction mixture of PhI=NTs, FeCl 2 , and terpyridine with ESI mass measurement.…”
supporting
confidence: 82%
“…A plausible reaction mechanism was proposed as shown in Scheme 1. Similar to previous reports, 5 iron catalysts could decompose PhI=NTs to generate an iron imido/ni-trene intermediate, which may undergo nitrene insertion into the C-H bond of an aldehyde to afford the corresponding amide. Attempts were made to characterize the reaction intermediate by monitoring the reaction mixture of PhI=NTs, FeCl 2 , and terpyridine with ESI mass measurement.…”
supporting
confidence: 82%
“…[12] When isoxepac was subjected to the optimized conditions under an atmosphere of O 2 for 24 h, the dehomologation reactionp roceeded to give 4a in 70 %yield. [13] Further derivatizations of 2j afforded various bioisosteres of carboxylic acids, such as hydroxamic acid 4b, [14] sulfonamide 4c, [15] and tetrazole 4d. [16] These reactions proceeded smoothly,g iving the desired products in 69 %, 63 %a nd 42 % yield, respectively.O verall,t his decarboxylation reaction enables us to access one-carbon reduced analogues of bioactive compounds.…”
mentioning
confidence: 99%
“…Subsequent works in our laboratory showed that a more practical version of this reaction with either tetrapyridyl complexes of Cu I or Fe II as the catalyst could be realized 113,114. In the case of the Cu I ‐mediated approach, we found that two distinct catalytic systems were required to achieve a broad substrate scope with moderate to excellent product yields of 47‐99%.…”
Section: Amination Of Formylic Ch Bondsmentioning
confidence: 85%